The scenario-based equity price impact induced by greenhouse gas emissions - Mark A. Weth; Markus Baltzer; Christoph Bertram; Jérôme Hilaire; Craig Johnston (Deutsche Bundesbank, 2024)
This paper proposes a forward-looking metric of transition risk that relates financial performance and incremental carbon costs at the firm level. To this end, we use a consistent dividend discount framework augmented with emission costs of firms and climate scenario projections from four large-scale integrated assessment models. Assuming a revision of market expectations from a baseline scenario to a net zero transition, we derive equity price impacts for 5,050 non-financial stock corporations covering half of global equity market capitalization and 17% of global greenhouse gas emissions. Our results suggest considerable disparities in firms' capacities to bear the scenario-implied costs of direct emissions. While especially fossil fuel energy firms and large emitters are exposed to potentially high devaluations and stranding, the majority of capitalization under review is exposed to moderate losses in a single-digit percentage range. We present the bandwidth of results across IAMs under alternative baseline scenarios and cost pass-through assumptions.
Keywords: G12; G15; Q42; Q51; Q54; 330; Transition risk; Asset pricing; Carbon price; Paris alignment; Stranded assets